Follicle Rescue From Prepubertal Ovaries After Recent Treatment With Cyclophosphamide—An Experimental Culture System Using Mice to Achieve Mature Oocytes for Fertility Preservation - Hao, Xia; Anastácio, Amandine; Viñals-Ribé, Laia; Santamaria Lacuesta, Ana; Diakaki, Christina; Alonso de Mena, Sara; Liu, Kui; Rodriguez-Wallberg, Kenny A. (Frontiers in Oncology, 2021)
Ovarian tissue cryopreservation is the only feasible method for fertility preservation in prepubertal girls that will undergo gonadotoxic chemotherapy. To date the only clinical use of cryopreserved tissue is by a later tissue re-transplantation to the patient. Clinical challenges in fertility preservation of very young patients with cancer include time constraints that do not allow to retrieve the tissue for cryopreservation before starting chemotherapy and the preclusion of future ovarian tissue transplantation due to the risk of reintroduction of malignant cells in patients with systemic diseases. To overcome these two challenges, we investigated using an experimental model the feasibility of retrieving secondary follicles from ovaries of prepubertal mice after cyclophosphamide (CPA) treatment in increasing doses 50, 75 and 100 mg/kg. The follicles were thereafter cultured and matured in vitro. The main outcomes included the efficiency of the method in terms of obtained matured oocytes and the safety of these potentially fertility preservative procedures in terms of analyses of oocyte competence regarding normality of the spindle and chromosome configurations. Our findings demonstrated that it was feasible to isolate and culture secondary follicles and to obtain mature oocytes from prepubertal mice ovaries recently treated with CPA. The efficiency of this method was highly demonstrated in the 100 mg/kg CPA group, with near 90% follicle survival rate after 12-days’ culture, similarly to control. Around 80% of the follicles met the criteria to put into maturation and more than 40% of them achieved metaphase II, with normal spindle and chromosome configurations observed. Suboptimal results were obtained in the 50 and 75 mg/kg CPA groups. These paradoxical findings towards CPA-dose might probably reflect a more difficult selection of damaged growing follicles from ovaries recently treated with lower doses of CPA, and a hampered ability to identify and discard those with reduced viability for the culture.